Caffeine increases both total work performed above critical power and peripheral fatigue during a 4-km cycling time trial - Felippe, L. C.; Ferreira, G. A.; Learsi, S. K.; Boari, D.; Bertuzzi, R.; Lima-Silva, A. E. (Journal of Applied Physiology, 2018)
The link between total work performed above critical power (CP) and peripheral muscle fatigue during self-paced exercise is unknown. We investigated the influence of caffeine on the total work done above CP during a 4-km cycling time trial (TT) and the subsequent consequence on the development of central and peripheral fatigue. Nine cyclists performed three constant-load exercise trials to determine CP and two 4-km TTs ~75 min after oral caffeine (5 mg/kg) or cellulose (placebo) ingestion. Neuromuscular functions were assessed before and 50 min after supplementation and 1 min after TT. Oral supplementation alone had no effect on neuromuscular function (P > 0.05). Compared with placebo, caffeine increased mean power output (~4%, P = 0.01) and muscle recruitment (as inferred by EMG, ~17%, P = 0.01) and reduced the time to complete the TT (~2%, P = 0.01). Work performed above CP during the caffeine trial (16.7 ± 2.1 kJ) was significantly higher than during the placebo (14.7 ± 2.1 kJ, P = 0.01). End-exercise decline in quadriceps twitch force (pre- to postexercise decrease in twitch force at 1 and 10 Hz) was more pronounced after caffeine compared with placebo (121 ± 13 and 137 ± 14 N vs. 146 ± 13 and 156 ± 11 N; P < 0.05). There was no effect of caffeine on central fatigue. In conclusion, caffeine increases muscle recruitment, which enables greater work performed above CP and higher end-exercise peripheral locomotor muscle fatigue. NEW & NOTEWORTHY The link between total work done above critical power and peripheral fatigue during a self-paced, high-intensity exercise is unclear. This study revealed that caffeine ingestion increases muscle recruitment, which enables greater work done above critical power and a greater degree of end-exercise decline in quadriceps twitch force during a 4-km cycling time trial. These findings suggest that caffeine increases performance at the expense of greater locomotor muscle fatigue.